Carica papaya seed extracts as an alternative treatment for contaminated water (2010)
Water is undoubtedly an essential resource for humanity and a key factor in the quality of life of populations worldwide. To decrease water turbidity, aluminum sulfate, an inorganic coagulant is used. However, this compound is unable to meet current demand. Therefore, alternative options from natural plant species are sought. Objective: Determine coagulant activity from aqueous, 10% ethanol, 10% acetic acid extracts obtained from dried and fresh papaya seeds (Carica papaya), in comparison with positive controls: aluminum sulfate Al2(SO4)3, wattle tree (Acacia mollissima), willow-leaf red quebracho (Schinopsis balansae) and chestnut (Castanea sativa). Methods: The laboratory flocculation test known as the jar test developed by the Department of Environmental applied microbiology, University of Hungliga Tekniska Högskolan, Stockholm, Sweden was employed. Results: All evaluated treatments presented a coagulant effect and were significant in comparison with untreated water (p < 0.0001). A greater coagulant effect was observed with dry seed ethanol extract at 2500 ppm, with a 66.45% effectiveness in comparison with aluminum sulfate. Conclusions: Obtained extracts from Carica papaya improve water’s physico-chemical properties in terms of turbidity reduction.